TATBIQU MABADI’ AL-KIYASAH FI FILEM ALLADIN ‘ALA ASASI NADHORIYATI GEOFFREY NEIL LEECH - Fauziyah, Ely; Chotimah, Dien Nur (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
Conversation is a social interaction consisting of the speaker and the addressee. The speaker should say politely to the addressee as well as vice versa. Politeness is an aspect of public interest in society. A letter could be said to be polite if it sufficed the six maxims, maxim of wisdom, generous, reward, humility, agreement and sympathy. The objectives of this research are 1) To describe the application of the principles of civility in the movie Aladdin based on the theory of Leech 2) To describe the degree of civility in the movie based on Leech. This research uses descriptive qualitative research. The data collection employed observation, reading and writing. The data analysis used the Mills and Huberman method, covering data reduction, presentation, and conclusion. Among the results are: 1) six principles of maxim in the movie cover: maxim of wisdom, generous, reward, humility, agreement and sympathy. 2) five degrees of civility in the movie involve: the degree of benefit and loss, choice, indirectness, authority, and social distance.